Digital-Based Public Services in Public Sector Organizations in Indonesia - Susilawati, Susilawati; Kurniawati, Kurniawati; Ilham, Dodi; Sunarsi, Denok; Haedar, Ahmad Wahidiyat (Jurnal Pallangga Praja (JPP), 2024)
This qualitative study explores the implementation of digital-based public services within the country’s public sector organizations. The research aims to investigate the current status, effectiveness, and challenges encountered in the deployment of digital platforms for public service delivery. Through a combination of interviews, focus group discussions, and document analysis, insights are gathered from various stakeholders, including government oficials, service providers, and citizens. Thematic analysis is employed to identify recurring patterns and underlying factors influencing the adoption and execution of digital public services. The findings reveal both strengths and weaknesses in existing digital platforms, as well as insights into citizen engagement levels, technological infrastructure, regulatory frameworks, and institutional capacities. Ultimately, this research contributes to the broader discourse on digital governance and public administration in Indonesia, emphasizing the need to leverage technology to enhance service delivery and promote citizen-centric governance practices.